Thermodynamic, environmental and sustainability calculations of a conceptual turboshaft engine under several power settings - Aygun, Hakan (Pergamon-Elsevier Science Ltd, 2022)
Application field of gas turbine engines has highly enlarged to different industries due to their significant properties. Constituting of one of several aero-engine types, turboshaft engines have drawn attention in recent years owing to rising usage areas. Therefore, it is very important to evaluate thermodynamic performance of turboshaft engines. In this study, a conceptual turboshaft engine with free turbine (TSEFT) was examined using performance, energetic, exergetic and environmental parameters at ten different power settings. In this context, effects of different operating points on thermodynamics behaviour of the engine can be assessed in terms of environmental impact and sustainability. According to performance assessments, power specific fuel consumption of TSE-FT was estimated between 0.3075 kg/kW.h and 0.588 kg/kW.h throughout operating points whereas its power changes between 379.33 kW and 1772.51 kW for the specified ranges. As for thermodynamic calculations, the lowest and highest exergy efficiency were found between 71.34% and 79.05% for the combustor and between 89.38% and 93.64% for power turbine (PT), respectively. Furthermore, exergy efficiency of the whole TSE-FT was computed between 13.4% and 25.62% whereas its environmental effect factor changes from 7.43 to 3.87 due to rising power setting. Moreover, specific irreversibility production (SIP) of the TSE-FT varies from 3.805 to 1.574 as the engine power increases. These findings show that exergetic evaluations for different running points could guide the related engineers to find out optimum power settings giving the highest sustainability level.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Turboshaft; Exergy; Gas turbine engine; Power settings; Sustainability